2008
DOI: 10.1051/forest:2008054
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations between wood quality traits of Pinus pinaster Ait

Abstract: Abstract• It is essential to understand how characteristics are related to each other in breeding programmes to select wood properties, in order to avoid that, in selecting for one trait, we are negatively affecting another. Moreover, measuring wood properties is time consuming and expensive.• This study assesses genetic and phenotypic correlations between wood density components and spiral grain of 46 half-sib families of Pinus pinaster in seventeen-year-old trees.• Results showed that genetic correlations fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
3
17
0
4
Order By: Relevance
“…Abdel-Gadir et al (1993) also achieved moderate positive correlations of LWP to density-related components (r = 0.38 to 0.63). Gaspar et al (2008b) also found a moderately positive correlation between these traits, although the correlation was slightly higher for LWD (r=0.59) than for EWD (r=0.49).…”
Section: Wood Density and Growth Componentsmentioning
confidence: 91%
See 2 more Smart Citations
“…Abdel-Gadir et al (1993) also achieved moderate positive correlations of LWP to density-related components (r = 0.38 to 0.63). Gaspar et al (2008b) also found a moderately positive correlation between these traits, although the correlation was slightly higher for LWD (r=0.59) than for EWD (r=0.49).…”
Section: Wood Density and Growth Componentsmentioning
confidence: 91%
“…For Pinus pinaster, Louzada (2003) also noticed a more important dependency of RD on EWD (r=0.959-0.960) than on LWD (r=0.521-0.708) and a moderate correlation between earlywood and latewood densities (r=0.291-0.507). On the other hand, Gaspar et al (2008b), also for Pinus pinaster, found a higher correlation of RD to LWD (r=0.72) than to EWD (r= 0.67) and a weak but positive correlation between earlywood and latewood densities (r=0.19). Abdel-Gadir et al (1993) stated that for Pseudotsuga menziesii in the juvenile period, RD was positively, moderately, and equally correlated with EWD and LWD (r=0.56), but in mature wood, the correlation was slightly higher with LWD (r=0.72).…”
Section: Wood Density and Growth Componentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies assessing genetic and phenotypic effects on wood characteristics in Pinus pinaster have indicated that earlywood characteristics are prone to genetic control, whereas latewood components are more strongly influenced by environmental factors (Gaspar et al, 2008a,b). These studies have also indicated the high heritability of wood density and the high genetic correlation between wood density and early wood density (Gaspar et al, 2008a), suggesting that breeding programmes to select this wood property by increasing either earlywood density, latewood percent, or both of these traits, would be profitable.…”
Section: Effect Of Site Tree and Stand Variables On Mean Tree Moe Trmentioning
confidence: 99%
“…Korelasi genetik sangat penting untuk memprediksi pengaruh dan efektifitas seleksi yang dilakukan terhadap suatu sifat (Gaspar, et al, 2008). Korelasi …”
Section: Korelasi Genetikunclassified